Students' Attitudes Toward Online Music Education During the COVID 19 Lockdown - Rucsanda, Mǎdǎlina Dana; Belibou, Alexandra; Cazan, Ana-Maria (Frontiers in Psychology, 2021)
Given the current pandemic context generated by COVID 19, important changes in the way specific subjects to music education are taught emerged, affecting not only the particularities of learning and teaching in individual courses, but also the other courses regarding group learning or theoretical subjects. Our research examines the students' attitudes towards online education, also presenting proposals for optimization and efficiency. The research was undertaken after an experience of a university semester in a lockdown context, and it aimed at undergraduate and master's degree students from music faculties in Romania. An important result was the mediating role of perceived utility of e-learning methods, perceived utility mediated the associations between compatibility of online methods and satisfaction towards the use of e-learning methods. The positive attitude towards e-Learning led to a higher perceived utility which, in turn, predicted a higher satisfaction towards e-Learning Although this period accentuated the fear of interaction with others, the anxiety related to the unknown, the intolerance of uncertainty did not predict the satisfaction towards the use of e-learning platforms. In conclusion, more educational initiatives are needed to promote remote teaching methods in music education. In the absence of similar research in our country, we considered that future research on this topic is needed.